2010
DOI: 10.31671/dogus.2019.160
|View full text |Cite
|
Sign up to set email alerts
|

Sağlık Harcamalarının Ekonomik Büyüme Üzerindeki Etkisi: OECD Ülkeleri Üzerine Bir Panel Regresyon Analizi

Abstract: Son yıllarda, ekonomik büyüme literatürüne yapılan teorik ve ampirik katkılar, ekonomik büyüme sürecinde beşeri sermayenin rolünü vurgulamaktadır. Ampirik çalışmaların büyük bir kısmı, genellikle eğitim ile ekonomik büyüme arasındaki ilişki üzerinde yoğunlaşmaktadır. Bu çalışmada ise, sağlığın ekonomik büyüme üzerindeki etkisi bir panel veri analizi ile test edilmektedir. Çalışma, 15 OECD ülkesine ilişkin 1990-2006 dönemi yıllık verilerini içerir. Analizlerde, diğer açıklayıcı değişkenlerin yanı sıra, kamu sağ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 10 publications
0
22
0
13
Order By: Relevance
“…Dreiger and Reimers ( 2005 ) studied the relationship between health expenditure and economic growth in 21 OECD countries for the period 1975–2001, and the results indicate that there is a long-run relationship between GDP per capita, health expenditure, and proxies for medical progress. Çetin and Ecevit ( 2011 ) tested the impact of health expenditure on economic growth of 15 OECD countries for the period 1990 to 2006. The results indicate that there is no significant relationship between health expenditure and economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Dreiger and Reimers ( 2005 ) studied the relationship between health expenditure and economic growth in 21 OECD countries for the period 1975–2001, and the results indicate that there is a long-run relationship between GDP per capita, health expenditure, and proxies for medical progress. Çetin and Ecevit ( 2011 ) tested the impact of health expenditure on economic growth of 15 OECD countries for the period 1990 to 2006. The results indicate that there is no significant relationship between health expenditure and economic growth.…”
Section: Empirical Literaturementioning
confidence: 99%
“…The empirical evidence showed that both health and education have positive significant effects on economic growth. Çetin and Ecevit [39] examined the effect of health on economic growth using a panel data analysis. This study consisted of annual data from 15 OECD countries for the period from 1990 to 2006.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Panel test statistics are calculated in the third phase using the following regression with the number of NT observations; in which, t refers to mean number of observations per horizontal section, and ρ refers to the mean lag length of each ADF (Çetin & Ecevit, 2010).…”
Section: Llc Unit Root Testingmentioning
confidence: 99%